Grammatical aspect influences event duration estimations: findings from Dutch - Flecken, Monique; Gerwien, Johannes (Proceedings of the ... annual conference of the Cognitive Science Society, 2013)
Flecken, M. & Gerwien, J. (2013). Grammatical aspect influences event duration estimations: findings from Dutch
Gesehen am 13.04.2022